Hydrophobic mullite ceramic hollow fibre membrane (Hy-MHFM) for seawater desalination via direct contact membrane distillation (DCMD) - Twibi, Mohamed Farag; Mohd Hafiz Dzarfan, Othman; Siti Khadijah, Hubadillah; Alftessi, Saber Abdulhamid; Mohd Ridhwan, Adam; Ahmad Fauzi, Ismail; Mukhlis, A.Rahman; Juhana, Jaafar; Raji, Yusuf Olabode; Mohd Haiqal, Abd Aziz; Mohd Nazri, Mohd Sokri; Huda, Abdullah; et al. (Elsevier Ltd, 2021)
A low-cost hydrophobic mullite hollow fibre membrane (Hy-MHFM) fabricated via phase inversion/sintering technique followed by fluoroalkyl silane (FAS) grafting is presented in this study. The prepared CHFMs were characterized before and after the grafting step using different characterization techniques. The pore size of the CHFM surface was also determined using ImageJ software. The desalination performance of the grafted membrane was evaluated in direct contact membrane distillation (DCMD) using synthetic seawater of varying salt concentrations for 2 h at various feedwater temperatures. The outcome of the evaluations showed declines in the permeate flux of the membrane at increasing feed concentration, as well as increased flux with increased feed temperature. The long-term stability of the membrane was achieved at time 20 h, feed temperature 60 °C, and permeate temperature 10 °C, the membrane achieved a salt rejection performance of about 99.99 % and a water flux value of 22.51 kg/ m2 h.